Public Sector Efficiency and Fiscal Austerity. (IMF Working Papers; Working Paper, 1998)
This paper uses a simple model to analyze the forces that determine the size of the public sector and the quality of workers employed in that sector. Workers are heterogeneous, and the public sector chooses an employment strategy that maximizes a social welfare function U(s, Y) that depends on the share of the labor force employed in public service s and private sector output Y. The government is fully informed about worker productivity. By examining the welfare properties of the possible outcomes, we are able to illuminate situations in which policies that seek to constrain the public sector may or may not improve economic efficiency.